Reduced sensitivity to sucrose in rats bred for helplessness: a study using the matching law - Sanchis-Segura, Carla; Spanagel, Rainer; Henn, Fritz A.; Vollmayr, Barbara (Behavioural pharmacology, 2005)
Anhedonia is a core symptom of depression. As it cannot be directly assessed in rodents, anhedonia is usually inferred from a reduced consumption of, or preference for, a reinforcer. In the present study we tried to improve the measurement of anhedonia by performing a detailed preference analysis based on the generalized matching law and tested its sensitivity in rats congenitally prone (cLH) or resistant (cNLH) to learned helplessness. According to the current interpretation of learned helplessness as a model for depression, a reduction in the rewarding properties of sucrose in cLH rats was hypothesized. Our results revealed that the ‘preference allocation’ index provided by this test, but not the traditional measures of sucrose consumption or preference over water, was significantly lower in cLH rats, and was correlated with the helpless behaviour as measured in an escape procedure. Therefore, it is clear that more subtle preference measures provided by the analysis of choice using the matching law principles are more sensitive and discriminative than those based on consumption of, or preference for, a single concentration of sucrose over water. Moreover, our data are in agreement with the proposed relationship between helplessness and sucrose preference, and support the usefulness of the cLH and cNLH rats as a model of depression.